Organic Amendment and Mulching Enhanced the Growth and Fruit Quality of Squash Plants (Cucurbita pepo L.) Grown on Silty Loam Soils - Mohamed Ahmed Youssef; Arwa Abdulkreem AL-Huqail; Esmat F. Ali; Ali Majrashi (Horticulturae, 2021)
Adoption of suitable organic fertilizers and soil mulching are useful tools to enhance soil quality, which will inevitably lead to improved growth and yield of crops. Little is known about the soil organic amendments and Azolla (Azolla pinnata) under soil organic mulching on the growth and yield of squash plant (Cucurbita pepo L.). A comparative study mainly focused on the impacts of organic fertilizer treatments on soil fertility and squash growth under wheat straw mulch was conducted on wooden boxes filled with silty loam soil. Wheat straw, as an organic mulch, and five organic-fertilization treatments were added to the soil. Wheat straw with a size of <2 cm was added to the soil surface with a 2 cm thickness. The fertilization treatments were: control (CO), chemical fertilizer (CF), compost (CT), vermicompost (VC), and dry Azolla (DA). Wheat straw mulch had positive effects on the soil properties, growth, and yield. The maximum fruit yield was obtained from the soil fertilized with DA under wheat straw mulch, while the lowest one was found in the control without mulching. Azolla and organic fertilizers showed a remarkable superiority over the mineral fertilization in increasing the soil fertility as well as the growth and quality of squash fruits; this superiority increased under the wheat straw mulching system. The application of recommended mineral fertilization (CF), compost (CT), vermicompost (VC), and dry Azolla (DA) under wheat straw mulch increased the soil available-N by 2, 20, 12, and 29%, respectively, above the control (CO), while these organic fertilizers without mulching increased the soil available-N by 11, 32, 26, and 48%, respectively. The production of vegetable crops such as squash plants requires the addition of organic fertilizers and mulching to increase yield and quality of fruits.